Linking HSP90 target occupancy to HSP70 induction and efficacy in mouse brain. (February 2016) - Thirstrup, Kenneth; Sotty, Florence; Montezinho, Liliana Christina Pereira; Badolo, Lassina; Thougaard, Annemette; Kristjánsson, Maj; Jensen, Thomas; Watson, Stephen; Nielsen, Søren Møller
Graphical abstract: Abstract: HSP90 (Heat shock protein 90) is a molecular chaperone protein ubiquitously expressed throughout all tissues in the body. HSP90 has been proposed as a target to increase turnover of pathological proteins leading to neurodegeneration in Huntington's disease, Parkinson's disease and Alzheimer's disease. The mechanism of how HSP90 inhibition leads to clearance of misfolded proteins is not fully understood. It may involve direct effects of inhibiting ATPase function, indirect effects by inducing the heat-shock-response resulting in upregulation of other chaperone proteins like HSP70 or a combination of both. In the current work we established a methodology to investigate the relationship between HSP90 target occupancy and HSP70 induction in vivo . We also characterized the acute effect of two different HSP90 inhibitors in the rTg4510 transgenic mouse model of Alzheimer's disease which displays a tau-mediated synaptic dysfunction. We show that reversal of synaptic impairments in this model can be obtained with a compound which has a high HSP70 induction capacity. The current developed assay methodologies may thus be of significant use in the further elucidation of the mechanism involved in the in vivo effect of HSP90 inhibition in models of neurodegeneration. Further on, the ability of HSP90 inhibitors to normalize synaptic dysfunction in an in vivo disease model of Alzheimer's disease could have therapeutic relevance and further strengthens the usefulness of this animal model to establish pharmacodynamic effect of HSP90 inhibition.